2008
DOI: 10.1007/s00464-008-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomized blinded trial shows relative thrombocytopenia in natural orifice translumenal endoscopic surgery compared with standard laparoscopy in a porcine survival model

Abstract: Significant differences in measured but not clinically apparent parameters were encountered. A potentially significant thrombocytopenia clinically was encountered in the NOTES group. The physiologic impact of NOTES procedures beyond the absence of abdominal incisions should be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In relation to platelet count, only the animals in the NOTES group presented a slight decrease, with no significant differences among groups. It is possible that the relative thrombocytopenia observed in the NOTES animals in our study and also observed by Bingener et al (15) could be secondary to the occurrence of bacteremia during the procedure. This hypothesis should be investigated in further studies.…”
Section: Discussionsupporting
confidence: 74%
“…In relation to platelet count, only the animals in the NOTES group presented a slight decrease, with no significant differences among groups. It is possible that the relative thrombocytopenia observed in the NOTES animals in our study and also observed by Bingener et al (15) could be secondary to the occurrence of bacteremia during the procedure. This hypothesis should be investigated in further studies.…”
Section: Discussionsupporting
confidence: 74%
“…There are only a few studies on the cardiopulmonary and immunologic effects of a basic NOTES procedure (transgastric NOTES peritoneoscopy vs laparoscopy), and little is known about the physiologic changes that may occur during a more complex surgical procedure using NOTES. [16][17][18][19][20] To our knowledge, this is the first report to evaluate the physiologic impact of transvaginal cholecystectomy compared with laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 Currently, most research focuses on the development of new devices and equipment and the prevention of infection; however, little research is focused on the trauma of NOTES, and the results of the few existing studies are contradictory. 7,8 In this study, using the present endoscopic devices and instruments, we found that the amount of trauma brought about by NOTES was not lower, but was greater than that brought about by laparoscopy. Some potential reasons for this include: (1) The damage NOTES causes to the stoma on the natural cavity wall was not less than the incisions on the abdominal wall made for laparoscopy; (2) NOTES increased the immune stress response for leading the bacterial translocation from the gastrointestinal tract into the abdominal cavity; (3) In NOTES, the pressure was difficult to regulate timely and accurately, and it fluctuated quickly and substantially; this may have increased the cardiac and circulatory burden.…”
Section: Discussionmentioning
confidence: 47%